ANZSI Newsletter indexing project: indexing the first 20 years (1973–92). (June 2018) - Russell, Mary
Abstract : Indexing the first 20 years of ANZSI Newsletters sounds like a straightforward task for a group of professional indexers, but serials indexing is never easy and this turned out to be a particular challenge. First there was a hunt to locate all the issues required for scanning. Then, the fact that there were two runs of newsletters with different titles and separate volume and page sequences meant devising locator formats to make it clear where exactly articles were located. Volunteers used different indexing software to complete their task. Editing, assisted by a thesaurus, and hyperlinking brought their own challenges. Mary Russell explains the process and how it could have been improved.